Green Investment Effect on Upstream Oil and Gas Activities in Indonesia - Sang Ayu Putu Rahayu; Puteri, Dina Silvia; Nathanael Bayu Ajie Pratomo (Arena Hukum, 2025)
Petroleum remains a key global energy source. Like coal, it significantly contributes to carbon emissions. In the era of energy transition, Indonesia faces mounting pressure to align its upstream oil and gas sector with global sustainability standards. The legal challenge lies in crafting a regulatory framework that both supports green investment and ensures environmental accountability. While Paramita (2022) and Wijaya (2022) have explored environmental governance in the energy sector, they primarily focus on renewable energy and overlook the regulatory transformation needed within fossil fuel industries. This study addresses the gap by examining how green investment interacts with upstream oil and gas activities in Indonesia and comparing its regulatory framework with those of Brazil and China, two countries with major emerging economies, using contrasting approaches to sustainable energy governance. Brazil emphasises environmental legislation in ecologically sensitive regions, while China exemplifies a centralised model of state-led green reform. This research employs a non-doctrinal socio-legal approach, combining statutory and comparative legal analysis with empirical fieldwork, including interviews with an Indonesian upstream oil and gas company. Findings reveal that Indonesia’s legal infrastructure remains underdeveloped in supporting low-carbon transition within its fossil energy sectors. Strengthening legal mechanisms and incentivising technological innovation are identified as critical strategies to align investment with environmental goals. This study contributes to legal science by offering a comparative lens on green regulatory transformation in resource-dependent economies. For international readers, it highlights the importance of sustainable legal reform in the context of fossil energy in three countries.